2011
DOI: 10.29333/ejgm/82761
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume as an Inflammatory Marker in Chronic Sinusitis

Abstract: Aim: Chronic rhinosinusitis (CRS) is characterized by persistent inflammation of the nasal and paranasal sinus mucosa. The pathogenesis of chronic sinusitis is not yet clearly understood. Recently, mean platelet volume (MPV) has been known as a simple inflammatory marker in inflammatory diseases. The aim of this study was to investigate the levels of hematological parameters such as red blood cells (RBC), haemoglobine (Hb), haematocrit (Htc), white blood cells (WBC), platelet (PLT), and mean platelet volume (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In chronic sinusitis, as reported by Koç et al [11], the platelet count is at the upper normal limit as compared to healthy subjects. Also, MPV is significantly higher in this group of patients.…”
Section: Mpv In Inflammationmentioning
confidence: 78%
See 1 more Smart Citation
“…In chronic sinusitis, as reported by Koç et al [11], the platelet count is at the upper normal limit as compared to healthy subjects. Also, MPV is significantly higher in this group of patients.…”
Section: Mpv In Inflammationmentioning
confidence: 78%
“…Also, MPV is significantly higher in this group of patients. This may suggest the involvement of blood platelets in the development and course of the disease [11].…”
Section: Mpv In Inflammationmentioning
confidence: 99%
“…[11] Koç et al demonstrated that MPV level was significantly higher in Chronic recurrent sinusitis compared to control group and PLT level was borderline higher in CRS group compared to control group. [12] S.Bozkur et al showed that there was no statistically significant difference between patients with appendicitis (complicated or uncomplicated) and those having no appendicitis with respect to MPV level. However, the complicated appendicitis group had a lower MPV value compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated MPV values have been attributed to emotional stress [ 40 ], increased sympathetic activity in patients with depression [ 17 , 38 , 41 , 42 ], and in patients with generalized anxiety disorder [ 35 ]. More recently, changes in platelet parameters have been linked to inflammatory processes, thus an abnormal MPV might indicate inflammation in psychiatric conditions [ 43 , 44 ]. However, the exact mechanism behind the association of changes in platelet parameters and affective disorders is not yet clearly established, since there have been results showing significantly decreased MPV in major depression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%